A protocol on information-motivation-behavioural skills risk of intensive phase treatment interruption among pulmonary tuberculosis patients in urban districts, Selangor - Suliman, Qudsiah; Md Said, Salmiah; Mohd Zulkefli, Nor Afiah; Lim, Poh Ying; Tan, Kit Aun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Despite advancement of treatment modalities, Tuberculosis (TB) treatment interruption rate has globally accelerating, calling for greater framework shifting towards psychosocial intervention. Similarly, Selangor state had reported the perturbing TB treatment interruption rate, which was figured persistently above 10% in the interval year of 2014 to 2018, thus signifies an empirical assessment on Information-Motivation-Behavioural skills (IMB) determinants of TB intensive phase treatment. This study aims to determine the time to intensive phase TB treatment interruption and its prognostic factors among newly diagnosed pulmonary Tuberculosis (PTB) smear positive patients in urban district Selangor. Methods: A multi-centric prospective cohort study will recruit 695 newly diagnosed PTB smear positive patients at treatment centres in urban districts, Selangor. This study will utilize validated self-administered questionnaire and standardised data collection form (PROFORMA). At baseline, we will elicit information on IMB models constructs, additionally on socio-demographics, health service factors and clinical characteristics. Meanwhile, four points follow up will be executed to retrieve information on treatment status and time varying effects of body weight, treatment side effects, symptoms improvement and internalised stigma. Finally, survival analysis will be computed to identify the time to intensive phase treatment interruption and its prognostic factors. Conclusion: This study will enlighten IMB model determinants of intensive phase treatment interruption, hence to endeavour psychosocial elements in designing time relevant public health strategies in TB case management.